Why EU-27 do not converge in cultural trade: evidence from convergence clubs and structural determinants - Cortés-Puya, Trinidad; Vázquez-La Hoz, Brenda; Galiano, Aida; Martín-Álvarez, Juan Manuel (Journal of Economic Studies, 2026)
Purpose Using Eurostat data for 2013–2023, we apply the Phillips and Sul log-t test and convergence-club algorithm to imports and exports of cultural goods. For non-convergent categories, multinomial logit models are estimated to identify the economic, digital, educational and demographic factors associated with club membership. Design/methodology/approach This paper examines whether EU-27 Member States follow common long-run trajectories in their trade of cultural goods and assesses the structural determinants of convergence or divergence across cultural categories. Findings Absolute convergence is rejected in several cultural goods categories, revealing multiple convergence clubs and persistent structural heterogeneity. GDP per capita, internet access, tertiary education and demographic structure significantly influence club membership, with effects differing between imports and exports. Practical implications The results suggest that cultural market integration in the EU is partial and shaped by structural differences, indicating the need for differentiated policy strategies. Originality/value This study provides the first dynamic convergence-club analysis of EU cultural goods trade and links endogenous trade trajectories to their structural determinants.
Keywords: cultural goods trade; convergence clubs; Phillips and sul methodology; structural heterogeneity; European Union